2012
DOI: 10.1021/jp3060735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerium Doping in the TiO2 Photoanode on the Electron Transport of Dye-Sensitized Solar Cells

Abstract: Rare earth element cerium (Ce) with variable valence states Ce 4+ /Ce 3+ is doped in the TiO 2 photoanode for dye-sensitized solar cells (DSSCs). The anatase crystalline phase keeps unchanged, while the crystalline size decreases slightly after Ce doping. The Ce positively changes the conduction band minimum of TiO 2 due to the unoccupied Ce-4f trap states in the band gap, and the Ce 4+ is reduced to Ce 3+ when electrons are injected in the photoanode. The ceriumdoped photoanodes with special electrochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 46 publications
4
63
0
Order By: Relevance
“…It also allows charge compensation mechanism to maintain a low concentration carriers [75]. We can list a series of hypervalent cations which have been successfully incorporated into the anatase crystal structure: W 6+ [76], Nb 5+ [77][78][79][80] [89]. The common observation is that hypervalent doping affects the energy of acceptor trap states.…”
Section: Dye-sensitized Solar Cells Principle: Role and Progress In Tmentioning
confidence: 99%
“…It also allows charge compensation mechanism to maintain a low concentration carriers [75]. We can list a series of hypervalent cations which have been successfully incorporated into the anatase crystal structure: W 6+ [76], Nb 5+ [77][78][79][80] [89]. The common observation is that hypervalent doping affects the energy of acceptor trap states.…”
Section: Dye-sensitized Solar Cells Principle: Role and Progress In Tmentioning
confidence: 99%
“…In order to improve the performance of the DSSCs, various treatments have been carried out, such as coated layer onto active materials [12] and doping of photovoltaic materials [13][14][15][16][17][18][19][20]. The materials are doped with metallic atoms, such as indium doped ZnO [13], cerium doped TiO 2 [14], stannum doped ZnO [15], boron doped ZnO [16], alluminium doped ZnO [17].…”
Section: Introductionmentioning
confidence: 99%
“…The materials are doped with metallic atoms, such as indium doped ZnO [13], cerium doped TiO 2 [14], stannum doped ZnO [15], boron doped ZnO [16], alluminium doped ZnO [17]. Doping can also be done by non-metallic materials, such as nitrogen doped TiO 2 [18][19][20], grapheme doped TiO 2 [21] and sulfur doped TiO 2 [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…162 In DSSCs, a number of studies have shown that incorporation of a rare earth dopant in the photoanode can improve the cell efficiency. 159,[163][164][165][166][167][168][169][170] The rare earth material is usually incorporated from the rare earth salt precursor into the TiO2 nanostructures during synthesis, 163,166,168,169,171 sometimes as a core/shell structure, 169 but has also been incorporated by soaking a prepared TiO2 photoanode into a rare earth salt solution followed by calcination 167 or by mixing rare earth nanoparticles with TiO2 nanoparticles followed by film preparation and calcination. 165 Upconverting, [172][173][174][175][176][177][178] 11.2% efficiency with a perovskite-based solar cell by incorporating 0.5% Yttrium into the TiO2 layer.…”
Section: Introductionmentioning
confidence: 99%